2016
DOI: 10.1039/c6ra04989c
|View full text |Cite
|
Sign up to set email alerts
|

Multi-block copolymers with fluorene-containing hydrophilic segments densely functionalized by side-chain quaternary ammonium groups as anion exchange membranes

Abstract: Design and fabrication of multi-block anion exchange membranes with fluorene-containing hydrophilic segments densely functionalized by side-chain quaternary ammonium groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…According to the Arrhenius equation, a linear function of ln σ versus 1000/ T is made, as shown in Figure b, It was found that the activation energy decreased sequentially with the increase of the cation grafting ratio, and the activation energies of the membranes for each grafting ratio were 16.7–21.28 kJ·mol –1 , which were all within the range of the activation energies of the membranes reported in the literature. The smaller the activation energy, the less energy is required to transport ions, so the ionic conductivity increases, which is also consistent with the above result that the conductivity increases sequentially with the increase of the cation graft ratio.…”
Section: Resultssupporting
confidence: 79%
“…According to the Arrhenius equation, a linear function of ln σ versus 1000/ T is made, as shown in Figure b, It was found that the activation energy decreased sequentially with the increase of the cation grafting ratio, and the activation energies of the membranes for each grafting ratio were 16.7–21.28 kJ·mol –1 , which were all within the range of the activation energies of the membranes reported in the literature. The smaller the activation energy, the less energy is required to transport ions, so the ionic conductivity increases, which is also consistent with the above result that the conductivity increases sequentially with the increase of the cation graft ratio.…”
Section: Resultssupporting
confidence: 79%
“…Noting that the water uptakes and swelling ratios of the 4C‐60‐Q membrane at varying temperatures are much higher, we calculate the number of bonded water per ammonium group (denoted as λ in Table ) of the x C‐ y ‐Q membranes to research the structure–activity relationship. The λ values ranged from 16.8 to 177.4, higher than most of the reported λ values at the same temperature . The parameters of PAES‐Q‐90, the asymmetric side‐chain‐type membrane, we reported previously are also listed in Table for comparison.…”
Section: Resultsmentioning
confidence: 83%
“…We have reported previously that the hydroxide ion conductivity, mechanical properties, and alkaline stability of the AEMs could be enhanced by introducing benzyltrimethyl ammonium side chain to the polymer backbone . Wang et al also reported a series of side‐chain‐type AEMs containing multiple quaternary ammonium groups based on a new monomer with four pendent 3,5‐dimethylphenyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Multiblock is another type of copolymer architecture that has been shown to produce phase-separated membranes. An advantage of designing multiblock hydrophilic–hydrophobic copolymers is that high molecular weight copolymers can be prepared from a range of molecular weights in the component materials. Research conducted on multiblock polysulfone (PSf) materials has produced copolymers from a variety of bisphenol monomers. Manipulation of the multiblock composition and the molecular weight of the component segments can tune the microphase separation .…”
Section: Introductionmentioning
confidence: 99%